Electric Field Cycling of Physisorbed Antibodies Reduces Biolayer Polarization Dispersion - Cinzia Di Franco; Eleonora Macchia; Michele Catacchio; Mariapia Caputo; Cecilia Scandurra; Lucia Sarcina; Paolo Bollella; Angelo Tricase; Massimo Innocenti; Riccardo Funari; Matteo Piscitelli; Gaetano Scamarcio; et al. (Advanced Science)
Abstract The electric dipoles of proteins in a biolayer determine their dielectric properties through the polarization density P. Hence, its reproducibility is crucial for applications, particularly in bioelectronics. Biolayers encompassing capturing antibodies covalently bound at a biosensing interface are generally preferred for their assumed higher stability. However, surface physisorption is shown to offer advantages like easily scalable fabrication processes and high stability. The present study investigates the effects of electric‐field (EF)‐cycling of anti‐Immunoglobulin M (anti‐IgM) biolayers physisorbed on Au. The impact of EF‐cycling on the dielectric, optical, and mechanical properties of anti‐IgM biolayer is investigated. A reduction of the dispersion (standard deviation over a set of 31 samples) of the measured P values is observed, while the set median stays almost constant. Hence, physisorption combined with EF cycling, results in a biolayer with highly reproducible bioelectronic properties. Additionally, the study provides important insights into the mechanisms of dielectric rearrangement of dipole moments in capturing biolayers after EF‐cycling. Notably, EF‐cycling acts as an annealing process, driving the proteins in the biolayer into a statistically more probable and stable conformational state. Understanding these phenomena enhances the knowledge of the properties of physisorbed biolayers and can inform design strategies for bioelectronic devices.